Goosegrass (Eleusine indica) resistant to multiple modes of action of herbicides in Brazil - da Silva Araújo, Lucas; Correia, Núbia Maria; Tornisielo, Valdemar Luiz; Veneziano Labate, Mônica Teresa; Tsai, Siu Mui; Carbonari, Caio Antônio [UNESP]; Filho, Ricardo Victoria (Cambridge University Press (CUP), 2023)
This study was developed based on a goosegrass (Eleusine indica (L.) Gaertn) population with resistance to multiple modes of action of herbicides (EPSPs inhibition - glyphosate; and ACCase inhibition - aryloxyphenoxypropionate chemical group), from Primavera do Leste, MT, Brazil. The objective was to identify possible mechanisms of resistance associated or not to sites of action of herbicides. Several experiments and analyses were carried out with the contribution of different laboratories and institutions. The results obtained allowed to conclude that: (i) the mutation Asp2078Gly conferred resistance to ACCase inhibitors, without overexpression of ACCase or changes in herbicide absorption and translocation; (ii) overexpression of EPSPs, mutations Thr102 and P106, and changes in absorption and translocation are not involved in the E. indica resistance to glyphosate; (iii) the metabolism of glyphosate in resistant E. indica plants requires further studies to elucidate the herbicide final destination in these plants. The mechanism of resistance of E. indica biotypes to ACCase-inhibiting herbicides was elucidated: it involves a change in the action site. However, the mechanism of resistance to EPSPs-inhibiting was not conclusive, denoting that some hypotheses should be tested, mainly regarding the metabolism of glyphosate in resistant plants.
Keywords: Eleusine indica; fenoxaprop-p-ethyl; glyphosate; haloxyfop-p-methyl; mechanisms of resistance